Similarities and differences of person in English and Uzbek languages - Usmonova Ruxsora Zoyir qizi, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
The examination of the degree of person is a subject of considerable academic interest , as it offers valuable insights into the similarities and differences of person . This article aims to explore the perspectives of both English and Uzbek scholars on this linguistic phenomenom . By delving into relevant theories and drawing upon examples from English and Uzbek literature , we endeavor to compare and contrast the terminologies and approaches employed in each language.